2022
DOI: 10.1124/jpet.121.001036
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Derived Myeloperoxidase and Hypochlorous Acid Critically Contribute to 20-Hydroxyeicosatetraenoic Acid Increases that Drive Postischemic Angiogenesis

Abstract: Compensatory angiogenesis is an important adaptation for recovery from critical ischemia. We recently identified 20-hydroxyeicosatetraenoic acid (20-HETE) as a novel contributor of ischemia-induced angiogenesis. However, the precise mechanisms by which ischemia promotes 20-HETE increases that drive angiogenesis are unknown.This study aims to address the hypothesis that inflammatory neutrophil-derived myeloperoxidase (MPO) and hypochlorous acid (HOCl) critically contribute to 20-HETE increases leading to ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…The evidence for heterogenous functions of neutrophils in disease stems partially from their discovered roles in neuronal and angiogenic repair in both spinal cord and optic nerve injury demonstrating direct and indirect protection [26, 27, 47, 50, 51]. These functions discovered in non-infection instances may be applicable to the demonstrated evidence of damaged neurons observed during chronic Toxoplasma infection [6, 7, 52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence for heterogenous functions of neutrophils in disease stems partially from their discovered roles in neuronal and angiogenic repair in both spinal cord and optic nerve injury demonstrating direct and indirect protection [26, 27, 47, 50, 51]. These functions discovered in non-infection instances may be applicable to the demonstrated evidence of damaged neurons observed during chronic Toxoplasma infection [6, 7, 52].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, aged neutrophils have upregulated transcription of the effector genes Bmf and Pdgfb and also Vegfa, and Kdr, noted for their roles in tissue repair. The overlap of these seemingly contradictory functions is steadily increasing with the recognition that the production of NETs and peroxidases are also required for tissue repair as well as effector mechanisms against pathogens [27,46,50]. This underpins the concept of innate immune cells being as critical to tissue homeostasis as they are in initiating immune responses and may pinpoint neutrophil flexibility as important not only in Toxoplasma infection but also in all models of CNS disease.…”
Section: Neuronal Regeneration Attempts During Chronic Infection Are ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent in vivo study showed that neutrophil-derived myeloperoxidase (MPO) activates proteins that drive postischemic angiogenesis [45].…”
Section: Immune and In Responsementioning
confidence: 99%